Contribution of Risk Factor Changes to the Decline in Coronary Incidence During the North Karelia Project: A Within-Community Analysis - SALONEN, JUKKA T; TUOMILEHTO, JAAKKO; NISSINEN, AULIKKI; KAPLAN, GEORGE A; PUSKA, PEKKA (International Journal of Epidemiology, 1989)
Salonen J T (Department of Community Health and General Practice, University of Kuopio, Kuopio, Finland), Tuomilehto J, Nissinen A, Kaplan G A and Puska P. Contribution of risk factor changes to the decline in coronary incidence during the North Karelia Project: A within community analysis. International Journal of Epidemiology , 1989, 18: 595–601. We investigated the contribution of risk factor changes to the decline in incidence of ischaemic heart disease between three five-year periods (1972–76, 1977–81, 1982–86) in a community-based cardiovascular disease (CVD) control programme, the North Karelia project. Random population samples of over 10000 people were examined in 1972, 1977 and 1982 and followed for five years. Population attributable benefits were estimated for each time period from reductions in excess risks associated with S–cholesterol, tobacco products per day and the mean of systolic and diastolic blood pressure which were entered in logistic models with age and sex. Changes in risk factors accounted in North Karelia for 89% and in the reference population for 20% of the decline in ischaemic heart disease from 1972–6 to 1977–81. In healthy people, risk factor reductions accounted in North Karelia for 100%, but in the reference population only for 23% of the decline. The decline was non-significant in both areas from 1977–81 to 1982–86. In subjects with either CVD or diabetes, there was no decline in North Karelia in either period, whereas 30% and 64% of the decline (ns) in the reference population in the two periods, respectively, was attributable to risk factor changes. These data suggest that although the decline in the incidence of ischaemic heart disease in North Karelia did not differ from that in the reference population it was largely attributable to risk factor reductions in the healthy population. The decline in the reference population appears to be associated with changes in lifestyle, secondary prevention activities and medical care.